The Vicious Circle of Poverty in Rural Society, Case Study of Tobacco Farmers in the Rural Area of Lombok Island - Nurjihadi, Muhammad; Dharmawan, Arya Hadi (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTPoverty is the cause of hunger, marginalization, neglectand the other social problems. Rural area, which most of its people work in agriculture, generally have more poor people than urban area. Lombok Island in NTB Province as one of the main producers of tobacco in Indonesia is one of the region with higher poor people percentage comparing to national percentage of poor people. This research aimed to know the pattern of vicious circle of poverty in tobacco farmers in Lombok Island. This research used qualitative method with descriptive approach. The number of respondents in this research are a hundred persons which were choosed by random sampling. While the research areas were choosed by purposive method. The research result revealed that the tobacco farmers in rural Lombok experienced the new pattern of vicious circle of poverty. Since the farmers had low level of capital, it encourage the farmers to make a collaboration with Tobacco Company which was create the dependence of farmers to tobacco commodity and Tobacco Company. Dependence on Tobacco Company make bargaining positions of farmerslowin transaction processwhich cause the farmers income become low. Low income lead the tobacco farmers to the ‘debt trap’ and low capital.Keywords: poverty, rural, farmers, tobacco, LombokABSTRAKKemiskinan adalah penyebab dari kelaparan, marginalisasi dan keterlantaran serta fenomena-fenomena negatif sosial lainnya. Kawasan pedesaan yang sebagian besar penduduknya bekerja di sektor pertanian umumnya memberikan sumbangan yang lebih besar dalam hal jumlah penduduk miskin dari pada kawasan perkotaan. Pulau Lombok di NTB sebagai penghasil utama tembakau di Indonesia adalah salah satu daerah dengan prosentase penduduk miskin lebih tinggi dari pada prosentase penduduk miskin nasional. Penelitian ini bermaksud untuk mengetahui pola lingkaran setan kemiskinan pada petani tembakau di Pulau Lombok. Penelitian ini menggunakan metode kualitatif dengan pendekatan diskriptif. Responden berjumlan seratus orang dipilih secara random sampling di wilayah penelitian yang ditentukan secara purposive. Hasil penelitian menunjukkan bahwa petani tembakau di pedesaan Pulau Lombok mengalami lingkaran setan kemiskinan dengan pola baru. Rendahnya tingkat modal petani mendorong petani untuk bermitra dengan perusahaan tembakau, kemitraan ini kemudian menciptakan ketergantungan petani pada komoditas tembakau dan perusahaan mitra, ketergantungan itu membuat posisi tawar petani lemah dalam proses transaksi yang mengakibatkan rendahnya pendapatan petani, pendapatan yang rendah membuat petani terjebak pada debt trap dan tidak mampu mengakumulasi modal, dengan demikian petani kembali memiliki modal yang sangat rendah.Kata kunci: kemiskinan, pedesaan, petani, tembakau, Lombok